Exploring Venus: next generation missions beyond those currently planned - Limaye, Sanjay S.; Garvin, James B. (Frontiers in Astronomy and Space Sciences, 2023)
As of mid-2023 at least ten missions are in development or being planned to explore Venus in the next two decades. Most of these have a combination of atmospheric chemistry and surface/interior scientific objectives and only a few directly address past and present habitability of Venus as a primary science goal. All of the missions employ previously flight-tested platforms – orbiters and general atmospheric probes, yet none (as of yet) plan to utilize longer-lived atmospheric platforms (e.g., balloons or airships) or landers. Thus several key questions about Venus will necessarily remain unanswered after the current wave of missions in development which will explore Venus starting in 2029 and continuing throughout the 2030s. This future-oriented perspective note outlines the major scientific questions that the next generation of missions to Venus should address for a better understanding of the planet as a system and provide a reliable comparative basis for the Venus-analogue exoplanets which can be investigated only by means of remote observations such as from the James Webb Space Telescope (JWST). This next generation of Venus missions may require long lived floating or flying atmospheric platforms operating at a range different altitudes, longer lived surface stations, and eventually samples of the atmosphere/cloud particles (aerosols) and surface returned to Earth laboratories. Although ideas for aerial platforms, long-lived landers, sample return missions are being conceptualized at present to be ready for upcoming international competed opportunities, they await further investment in technologies to provide the combination of scientific measurement capabilities and flight-system performance.